A history of war in 100 battles - Overy, R. J. (Oxford University Press, 2014)
"Their very names--Gettysburg, Waterloo, Stalingrad--evoke images of great triumph and equally great suffering, moments when history seemed to hang in the balance. Considered in relation to each other, such battles--and others of less immediate renown--offer insight into the changing nature of armed combat, advances in technology, shifts in strategy and thought, as well as altered geopolitical landscapes.